Denmark’s Depth Model version 2.0 – Improved compilation of bathymetric data within the Danish waters - Schwenger, Lasse M.; Kristmar, Kristian V.; Masetti, Giuseppe; Sigaard Granding, Philip; Langdahl, Kasper (The International Hydrographic Review, 2025)
Denmark’s Depth Model version 2.0 (DDM v2.0) is the latest iteration of a Digital Bathymetric Model (DBM) for Danish waters, offering a grid resolution of 50 meters. The compilation integrates hundreds of survey datasets, including both modern and historical sources, as well as satellite-derived and crowdsourced bathymetric data. The model is referenced to Mean Sea Level (MSL) datum and – due to the adopted compilation process – is not designed for safety of navigation. DDM v2.0 is accessible through the Danish Geodata Agency’s website and constitutes a significant contribution to the European Marine Observation and Data Network (EMODnet) Bathymetry initiative.